Applications of stochastic optimization to sovereign institutions 2 - Kreuser, Jérôme L. (Henry Stewart Talks, 2012)
Properties captured by DSP models, Marginal value solution information and sensitivity analysis, Visualization is the key to unlocking complexity, An example with the Reserve Bank of India with 21 risk constraints mapping institutional strategic objectives